RETRACTED: Akt Inhibition Enhanced the Growth Inhibition Effects of Low-Dose Heavy-Ion Radiation via the PI3K/Akt/p53 Signaling Pathway in C6 Glioblastoma Cells - Huang, Ke; Zhao, Wei; Wang, Xuqiao; Qiu, Yingfei; Liu, Zelin; Chen, Rui; Liu, Wei; Liu, Bin (Frontiers in Oncology, 2021)
Background: Glioma is one of the deadliest tumors of the nervous system and commonly used treatment protocols hardly ever lead to tumor control. Low-dose carbon-ion radiation has a great superiority of targeting cancer and tumor cells, but the mechanism of the growth inhibition effect induced by heavy-ion radiation via the PI3K/Akt signaling pathway remains unknown, and the growth inhibition effect of heavy-ion radiation in C6 cells was not pronounced. Methods: Carbon-ion radiation was used to determine the effect of heavy-ion radiation on C6 cells, and suppression of Akt was performed using perifosine. MTT assays were carried out to investigate the optimal treatment concentration of perifosine. The clone formation assays were performed to investigate the grow inhibition effect of carbon-ion radiation and the effect of radiation with Akt inhibition. Lactate dehydrogenase (LDH) release, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content were detected to investigate oxidative stress levels. The expression level of proteins in the PI3K/Akt/p53 signaling pathway were assessed by Western-blot analysis. Results: Intervention concentration of perifosine (IC10=19.95 μM) was determined by MTT assay. Clone formation assay was carried out and no statistical evidence on the inhibition of cell growth was observed after treatment with heavy-ion irradiation, whereas perifosine enhanced the inhibition effect. Heavy-ion radiation induced LDH release, increased the level of MDA and decreased the activity of SOD. Correspondingly, Akt inhibition promoted these processes. Heavy-ion radiation treatment downregulated the expression of Akt, while upregulated the expression of Bcl-2. The expression level of p53 and Bcl-2 were significantly upregulated and Bax expression was downregulated. Moreover, the expression tendency among pAkt, Bcl-2 and Bax was reversed when treated with perifosine. Caspase 3 expression was upregulated in all radiation groups. Conclusions: The growth inhibition effect of low-dose heavy-ion irradiation was not markedly in C6 cells and Akt inhibition induced by perifosine enhanced the growth inhibition effect via proliferation inhibition, apoptosis, and oxidative stress. In summary, Akt inhibition enhanced the effect of heavy-ion radiation, and PI3K/Akt/P53 signaling pathway might be a critical pathway being involved in the process.